Efficient Synthesis, Structure, and Complexation Studies of Electron‐Donating Thiacalix[n]dithienothiophene1. (16th January 2015) - Inoue, Ryota; Hasegawa, Masashi; Nishinaga, Tohru; Yoza, Kenji; Mazaki, Yasuhiro
Abstract A series of thiacalix[n]dithiothiophenes (n=4–10) was prepared by a facile method and X‐ray analysis was used to determine the molecular structures of square‐ (4‐mer) and pentagonal‐shaped macrocycles (5‐mer). In the cyclic voltammograms, reversible multielectron redox processes, which are due to electronic delocalization, were observed at low oxidation potentials. The cyclic 4‐mer acted as a "Janus‐head" cavitand for two C60 molecules, whereas the 5‐ and 6‐mer formed stable 1:1 complexes with C60 .